Transplantation of exogenous mitochondria mitigates myocardial dysfunction after cardiac arrest - Zhen Wang; Jie Zhu; Mengda Xu; Xuyuan Ma; Maozheng Shen; Jingyu Yan; Guosheng Gan; Xiang Zhou (eLife)
The incidence of post-cardiac arrest myocardial dysfunction (PAMD) is high, and there is currently no effective treatment available. This study aims to investigate the protective effects of exogenous mitochondrial transplantation in Sprague-Dawley (SD) rats. Exogenous mitochondrial transplantation can enhance myocardial function and improve the survival rate. Mechanistic studies suggest that mitochondrial transplantation can limit impairment in mitochondrial morphology, augment the activity of mitochondrial complexes II and IV, and raise ATP level. As well, mitochondrial therapy ameliorated oxidative stress imbalance, reduced myocardial injury, and thus improved PAMD after cardiopulmonary resuscitation (CPR).